Biochemical and histological investigation of azathioprine and melatonin in rats - Hussein, AΑ; Ahmed, MΗ; Mustafa, NG (Journal of the Hellenic Veterinary Medical Society, 2024)
ABSTRACT Azathioprine (AZA) is a purine antagonist, also known as Imuran or Azapress, is a commonly prescribed immunosuppressive drug that is used in the management of many conditions (cancer, inflammatory bowel diseases, post-transplant immunosuppression, and various autoimmune diseases). However, their therapeutic role has been under debate because of their hepatotoxicity. Monitoring liver function in patients with hepatic impairment who are taking AZA is recommended. Melatonin (MEL) is a hormone usually produced at night by the pineal gland that acts to regulate the day and night cycle. Melatonin in supplements is usually made in a lab and is frequently used for the treatment of insomnia caused by shift work and jet lag. It is a well-known natural antioxidant, improving the hepatic detoxification system. There are numerous studies investigating the effects of MEL on liver injuries. Melatonin could control proliferation, reducing apoptosis, inflammation, and suppressing autophagic cell death in different pathophysiological conditions. The current study was undertaken to determine whether MEL could improve and ameliorate structural and biochemical changes in the liver that were induced by AZA. The 24 male adult rats were grouped as follows: The first group (G1) was given normal saline orally for 4 weeks and was listed as a control, while the second group (G2) was given AZA orally (20 mg/kg B.Wt.) for 4 weeks. MEL (10 mg/kg, B.Wt.) was given to the third group (G3) for four weeks. The fourth group (G4): given AZA (20 mg/kg B.Wt.) and MEL (10 mg/kg B.Wt.) for 4 weeks. Liver sections of the AZA-treated group showed degeneration and necrosis of hepatocytes with increased numbers of kupffer cells. Group 4 showed the normal architecture of liver tissue with increased numbers of kupffer cells. The serum biochemical profiles showed an increase in serum aspartate (AST) and alanine aminotransferase (ALT) enzymes, and a reduction in albumin and total protein in the group treated with AZA, while the liver function tests in the third and fourth groups showed a nonsignificant difference from the control group. We concluded from the results of this study that AZA induces structural and biochemical changes in the liver, and these effects could be improved by the administration of MEL in the last group. Keywords: Azathioprine; Biochemical; Histological; Liver; Melatonin.